ANALISIS SWOT : MODEL STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN NILA - Aji Septian Tricahya; Hartono Hatono; Hani Damayanti Aplilani (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This research aims to formulate an appropriate business development strategy model in developing tilapia cultivation businesses in Tulung Balak village. The research method used is descriptive with a qualitative approach. The research location is the Alkalam fishery in Tulung Balak village. Informants were selected by purposive sampling. Data collection techniques use observation, in-depth interviews, and documentation. The results of the research show that the appropriate strategy model for alkalam fisheries is the SO strategy, the SO strategy is a strategy that maximizes strength in exploiting opportunities. Internal business strengths such as income from selling seeds and stable harvests, low operational costs because it uses a semi-intensive cultivation system and daily labor, various payment methods, friendly service and fast response, using a water-powered mill to increase the oxygen supply in the pond, management good water system, use of various types of feed according to fish size, good and routine fish health management, good water waste management, independent feed production. Can be used to capture opportunities such as maintaining good and harmonious relationships between owners and employees, between companies and suppliers, and between companies and consumers, Developing the use of technology in producing homemade feed, Maintaining customer trust by improving the quality and quality of products using raw materials quality, sensitive to changes in customer desires and carrying out quality control, consumers can make payments via e-wallet and bank transfer.